NaCl- and Na2SO4-induced salinity differentially affect clay soil chemical properties and yield components of two rice cultivars (Oryza sativa L.) in Burundi - Irakoze, Willy; Prodjinoto, Hermann; Nijimbere, Séverin; Bizimana, Jean Berchmans; Bigirimana, Joseph; Rufyikiri, Gervais; Lutts, Stanley (MDPI, 2021)
Salinity may strongly influence the interaction between plant roots and surrounding soil, but this has been poorly studied for sodium sulfate (Na2SO4). The aim of this study was to investigate the effect of sodium chloride (NaCl) and Na2SO4 salinities on the soil chemical properties as well as rice physiological- and yield-related parameters of two contrasted cultivars (V14 (salt-sensitive) and Pokkali (salt-resistant)). Pot experiments were conducted using soil and electrolyte solutions, namely NaCl and Na2SO4, inducing two electrical conductivity levels (EC: 5 or 10 dS m−1) of the soil solutions. The control treatment was water with salt-free tap water. Our results showed that soil pH increased under Na2SO4 salinity, while soil EC increased as the level of saline stress increased. Salinity induced an increase in Na+ concentrations on solid soil complex and in soil solution. NaCl reduced the stomatal density in salt-sensitive cultivar. The total protein contents in rice grain were higher in V14 than in Pokkali cultivar. Saline stress significantly affected all yield-related parameters and NaCl was more toxic than Na2SO4 for most of the studied parameters. Pokkali exhibited a higher tolerance to saline stress than V14, whatever the considered type of salt. It is concluded that different types of salts differently influence soil properties and plant responses and that those differences partly depend on the salt-resistance level of the considered cultivar.